Art Is (Not) Knowledge. A question of Hegelian terminology - Illetterati, Luca (Aesthetica Preprint, 2021)
In a seminal paper published in 1974 and titled ‘On Artistic Knowledge. A Study in Hegel’s Philosophy of Art’, Albert Hofstadter focuses on the cognitive value of art within Hegel’s philosophy. In particular, Hofstadter aims at explaining in what sense we should understand the Hegelian idea that art is a deeper form of knowledge than the sciences. In my paper I intend to show how the question becomes clearer if we take into account the specific terminology that Hegel uses and in particular the fundamental distinction between the German terms ‘kennen’ and ‘wissen’. In the English language, these terms tend to deflate into one indistinct notion, namely that of ‘knowledge’, which blurs this conceptual distinction.